1998
DOI: 10.1021/la980462e
|View full text |Cite
|
Sign up to set email alerts
|

Control of Structural Order in Self-Assembled Zirconium Alkylphosphonate Films

Abstract: Monolayer films of zirconium alkylphosphonates Zr(O3P−R) (R = C14H29, C18H37, C22H45) with different long-chain alkyl groups have been prepared by adsorption from dilute solutions of the corresponding alkylphosphonic acids (molecular self-assembling) onto different primer mono- and multilayers on gold and silicon substrates. The surface orientation of the film molecules and the film structure has been investigated as a function of the hydrocarbon chain length of the adsorbate molecules, the composition and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…The highly ordered SAM can be responsible for significant changes in physical particle surface properties and influence the tendency of the particles to agglomerate via interparticle alkyl-chain-bilayer formation, and thus destabilization of nanoparticle dispersions, which is undesirable for many applications, such as nanocomposite preparation. This can be a problem for facets of larger size (upper nm range to macroscopic scale) as it is the case for zirconiumalkylphosphonate-films [23] , because the stability of the alkyl bilayer is given by the number of Van der Waals – interacting alkyl chains. However this occurs also for very small nanoparticles, as described in literature, a strong intercalation of chains can occur to compensate the high surface curvature, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly ordered SAM can be responsible for significant changes in physical particle surface properties and influence the tendency of the particles to agglomerate via interparticle alkyl-chain-bilayer formation, and thus destabilization of nanoparticle dispersions, which is undesirable for many applications, such as nanocomposite preparation. This can be a problem for facets of larger size (upper nm range to macroscopic scale) as it is the case for zirconiumalkylphosphonate-films [23] , because the stability of the alkyl bilayer is given by the number of Van der Waals – interacting alkyl chains. However this occurs also for very small nanoparticles, as described in literature, a strong intercalation of chains can occur to compensate the high surface curvature, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The coupling agent dodecylphosphonic acid was synthesized via an Arbuzov -reaction and hydrolysis of the obtained phosphonate was carried out applying literature-known procedures [22,23] .…”
Section: Methodsmentioning
confidence: 99%
“…Various structures and compositions were investigated, especially for the alkyl phosphonates, because it has previously been shown that alkyl chain length influences the order and stability in adsorbed monolayers. 53,54 Immersion times were 5 min in the phosphonate solution, 1 min in Zr͑IV͒, and 30 min in methanol for each phosphonate. As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…54 Thus, the dramatically better inhibition for ZODP suggests that the order of the thin film may play a key role in its effectiveness. With this in mind, we focused on the optimization and characterization of ZODP thin films for the remainder of the investigations.…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning of the research on the SAM layers of this group, the experts revealed that the functional group binds onto a native, more-or-less hydrated metallic oxide layer. This is an acid–base catalyzed condensation which goes in three steps: (1) hydrogen bond forms between the phosphonic acid head group and the metal surface; (2) there is an acid–base catalyzed reaction between the P–OH groups and the –OH groups on the surface, and mono- and bidentate bonds as well as salt and water are formed; 3) the third step produces tridentate bonds via hydrogen bond formation between the phosphoryl oxygen and the surface hydroxyl groups, which is responsible for the self-assembling of the molecule [ 112 , 113 , 114 , 115 ].…”
Section: Sam Layers Built From Different Chemicalsmentioning
confidence: 99%